Game Floating City Islands untuk Meningkatkan Kompetensi Pengetahuan dan Minat Belajar Matematika pada Masa Pembelajaran Jarak Jauh - Ardiyanto, Doni Setiyo (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to describe the effectiveness of using the "Floathing City Islands Game" in learning mathematics during the Distance Learning (PJJ) period to increase knowledge competence and interest in learning mathematics. The method used in this paper is descriptive quantitative research. The subjects in this study were 32 class VIII C students of SMPN 1 Tempuran who studied through online PJJ. The learning innovations that are made contain a recreative element, namely an educational game that is given “Floathing City Islands”. In games based on material or math questions for preparation for the Year End Assessment (PAT). The game was developed using the Articulate Storyline 3 application. The results showed that (a) “Floating City Islands” can be applied to meaningful and fun mathematics learning during PJJ or BDR. (b) This game is effective for increasing students’ knowledge competence and learning interest.